1971
DOI: 10.1126/science.172.3985.850
|View full text |Cite
|
Sign up to set email alerts
|

DNA (Cell Number) in Neonatal Brain: Second Generation (F 2 ) Alteration by Maternal (F 0 ) Dietary Protein Restriction

Abstract: Female rats were maintained on a protein-restricted diet 1 month prior to mating and throughout pregnancy. Their female offspring were maintained on a normal diet from birth or from weaning and were mated with normal males. The second generation offspring at birth still had significantly lower cerebral weight and total cerebral DNA (cerebral cell number).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

1975
1975
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 11 publications
2
33
0
1
Order By: Relevance
“…For example Zamenhof et al (1971) and Cowley and Griesel (1966) have shown that if rats are malnourished before or during gestation, brain sizes, maturation and cognitive performance of two subsequent generations are reduced even if all descendants are fed a normal diet. More recent evidence shows that the offspring of male mice, who consumed a low protein diet during late childhood (from weaning until sexual maturity), have elevated expression of many genes in liver tissue and exhibit changes in cytosine methylation (Carone et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example Zamenhof et al (1971) and Cowley and Griesel (1966) have shown that if rats are malnourished before or during gestation, brain sizes, maturation and cognitive performance of two subsequent generations are reduced even if all descendants are fed a normal diet. More recent evidence shows that the offspring of male mice, who consumed a low protein diet during late childhood (from weaning until sexual maturity), have elevated expression of many genes in liver tissue and exhibit changes in cytosine methylation (Carone et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While transgenerational effects of nutritional deprivation during adolescence may seem farfetched from the point of view of a social scientist, there exists ample evidence from mice models (and some on humans) showing that the effects of nutritional shocks can indeed persist for several generations. For example Zamenhof et al (1971) and Cowley and Griesel (1966) have shown that if rats are malnourished before or during gestation, brain sizes, maturation and cognitive performance of two subsequent generations are reduced even if all descendants are fed a normal diet. More recent evidence shows that the offspring of male mice, who consumed a low protein diet during late childhood (from weaning until sexual maturity), have elevated expression of many genes in liver tissue and exhibit changes in cytosine methylation (Carone et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…5). Nutritional protein restriction is known to reduce DNA in offspring (20). The differences in DNA and RNA content between the high and low protein seeds were comparable to their differences in fresh weight ( Fig.…”
Section: Methodsmentioning
confidence: 63%